Faktor-Faktor yang Mempengaruhi Tingkat Keselarasan Laporan Tahunan dengan Rerangka Integrated Reporting - Akhmad Sigit Adiwibowo; Fita Ifnapiya (Universitas Pamulang, 2020)
This study aims to determine and obtain empirical evidence of the influence of audit committees, the proportion of independent commissioners, and ownership structure on the alignment level of the annual report. This research uses quantitative research using descriptive methods. The population in this study includes 69 manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling by obtaining 57 data. The analytical method using multiple linear regression models analysis was processed and analyzed using the IBM Statistical Package for Social Sciences (SPSS) version 25 program. The results showed that managerial ownership has a negative and significant effect on the alignment level of the annual report with integrated reporting framework and the audit committee, proportion of independent commissioners, institutional ownership and foreign ownership does not affect the alignment level of the annual report. Based on simultaneous hypothesis testing shows of the audit committee, the proportion of independent commissioners, managerial ownership, institutional ownership, and foreign ownership jointly affect the alignment level of the annual report. Keywords: Alignment Level of Annual Report with Integrated Reporting; Audit Committee; Proportion of Independent Commissioner; Ownership structure